STING-dependent interferon-λ1 induction in HT29 cells, a human colorectal cancer cell line, after gamma-radiation - Chen, J; Markelc, B; Kaeppler, J; Ogundipe, V; Cao, Y; McKenna, G; Muschel, R (Elsevier, 2018)
To investigate the induction of type III interferons (IFNs) in human cancer cells by gamma-rays.Type III IFN expression in human cancer cell lines after gamma-ray irradiation in vitro was assessed by reverse transcription-quantitative polymerase chain reaction and enzyme-linked immunosorbent assay. Signaling pathways mediating type III IFN induction were examined by a variety of means, including immunoblotting, flow cytometry, confocal imaging, and reverse transcription-quantitative polymerase chain reaction. Key mediators in these pathways were further explored and validated using gene CRISPR knockout or short hairpin RNA knockdown.Exposure to gamma-rays directly induced type III IFNs (mainly IFNL1) in human cancer cell lines in dose- and time-dependent fashions. The induction of IFNL1 was primarily mediated by the cytosolic DNA sensors-STING-TBK1-IRF1 signaling axis, with a lesser contribution from the nuclear factor kappa b signaling in HT29 cells. In addition, type III IFN signaling through its receptors serves as a positive feedback loop, further enhancing IFN expression via up-regulation of the kinases in the STING-TBK1 signaling axis.Our results suggest that IFNL1 can be up-regulated in human cancer cell lines after gamma-ray treatment. In HT29 cells this induction occurs via the STING pathway, adding another layer of complexity to the understanding of radiation-induced antitumor immunity, and may provide novel insights into IFN-based cancer treatment.